ANALISIS KERJASAMA AUSTRALIA DAN SELANDIA BARU DALAM ‘TRANS-TASMAN TRAVEL ARRANGEMENT’ - Annisa Mediana Shafa (Universitas 17 Agustus 1945 Jakarta, 2020)
Australia and New Zealand's cooperation in the Trans-Tasman Travel Arrangement (TTTA) which was agreed in 1973 made it easier for both countries to travel freely, both for those who only wanted to travel temporarily or stay permanently. The basic fixed rules that were first introduced as the requirements for both countries to travel were the indigenous people of Australia and New Zealand or the original Australian and New Zealand passport holders. Australia has changed the TTTA rules several times by adding a number of requirements to minimize the misuse of free travel, namely exemption from checking passports to applying universal visas. After Australia;s changes, it was then followed by New Zealand's changes in the New Zealand Immigration Act. This collaboration has a large impact on both countries, namely in terms of education, social benefits, health, and others.